Keeping It in the Family: Student to Degree Match - Richard J. Murphy; Pedro Luís Silva (Institute of Labor Economics (IZA), 2024)
This paper examines systematic inequalities in the match between students and the university degree they apply to, and enroll in. Using linked administrative data on the population of Portuguese applicants we create a transparent and continuous measure of student-to-degree match employing minimal assumptions. We find that students who are the first in the family to attend post-secondary education consistently match to lower quality degrees across the entire achievement distribution. In contrast, only the highest achieving female students relatively undermatch. These gaps are larger at the application stage. We explore the role of student preferences and the consequences for intergenerational mobility.
Keywords: I22; I23; I28; 330; higher education; educational economics; college choice; mismatch; undermatch